Rapid Mapping for Simple Flood Mitigation Using Commercial Drone at Way Galih Village, Lampung, Indonesia - Rohman, Arif; Prasetya, Dwi Bayu (Universitas Muhammadiyah Surakarta, 2019)
The process to alleviate flood risk, especially flood from a river that occurs excessively in Indonesia, requires a new approach. The attempt to reduce the risk along with the development of technology is by utilising commercial drones and rapid mapping methods for mapping flood plain area. With the rapid mapping method, the flood mitigation process in the village area can be done quickly. The activity carried out was to map the location of possible flooding in the Way Galih Village and case analysis to determine the location of the biogas digester together with the village government authority. The results of the study show that the data acquisition process and aerial photo processing can be carried out within one day and the village policymaker can quickly make policies and decisions about where to place the biogas digester.